ADVANCING PUBLIC HEALTH NUTRITION THROUGH SUSTAINABLE FISHERIES - Mohanty, B. P. (Journal of the Inland Fisheries Society of India, 2024)
Public health nutrition (PHN) focuses on improving human health and preventing diseases through good dietary practices and nutritional interventions to address malnutrition (that includes both under- and overnutrition), obesity and food securityat population level. It includes two key areas: Community nutrition that involves planning and implementing nutrition policies and interventions for communities (like maternal nutrition programs), schools (like midday meal programs) and other workplaces, and the Clinical nutrition that focusses on assessment and management of nutritional needs of individuals with chronic health issues like diabetes, cardiovascular diseases, food allergy and other metabolic disorders through medical nutrition therapy.Thus, while community nutrition works on broader health strategies for larger groups, communities at population level, clinical nutrition is personalized dealing with specific medical needs of individuals.